PENGEMBANGAN MEDIA AUDIO VISUAL PASSING BAWAH DALAM PERMAINAN BOLA VOLI SISWA KELAS VI SD INPRES OEBA I KUPANG - Lukas M. Boleng; Veramtya M. M. Flora Babang; Ratib Suaib (Nusa Cendana University, 2020)
ABSTRACT This research is research and development. The subjects in this trial were students of class VI SD Inpres Oeba 1 Kupang, small scale trials totaling 12 children and large scale trials totaling 36 children and had never received material with this audio visual media. The instruments used were questionnaires and audio visual media products. To analyze data, use descriptive statistics with a percentage. In small scale trials it was found that many 7 (58.33%) children had